Theoretical Study of CO, NO, NO2, Cl2, and H2S Adsorption Interactions with PdO–Graphene Composites for Gas Sensor Applications - Piumantha Samaranayake; Azeez Ahamed; Visal de Silva; Nadeesha Manohari Wickramage; Muhammad Raziq Rahimi Kooh; Roshan Thotagamuge (Micromachines)
Gas sensors play a vital role in detecting gases in the air, converting their concentrations into electrical signals for industrial, environmental, and safety applications. This study used density functional theory methods to explore the mechanism and sensitivity of a PdO–graphene composite sensor towards various gases (CO, NO, NO2, H2S, and Cl2). All calculations, including structure, energy, and frequency optimizations, were performed using the Gaussian software with appropriate configurations and basis sets. Key parameters such as the adsorption energy, charge transfer, energy gap, density of states, and HOMO–LUMO were computed for each gas molecule on the PdO–graphene composite. The sensitivity and recovery time were also evaluated. The findings show that CO exhibited the highest adsorption energy (−6.5513 eV) and adsorbed with a noticeable tilt toward the PdO–graphene plane, indicating a strong interaction, and H2S exhibited the lowest adsorption energy, calculated as −2.0110 eV. H2S demonstrated the highest charge transfer of 0.445 e and an energy gap of 3.1321 eV, and CO exhibited the lowest charge transfer, calculated as 0.036 e, while NO2 demonstrated the lowest energy gap, determined to be 2.5004 eV. NO2 demonstrated the highest sensitivity, at 1285.2% for the PdO–graphene composite, and the lowest were Cl2 and H2S, with a sensitivity of 99.9%, while Cl2 had the shortest recovery time of 7.66 × 10−11 s, and CO had the longest recovery time of 2.55 × 10−10 s. The addition of PdO significantly enhanced the interaction strength between the adsorbed gas molecules and the graphene sheet when compared to Pd–graphene or pure graphene. This enhancement is reflected in the increased adsorption energy and band gap and low charge transfer, which significantly influenced the electrical conductivity of the PdO–graphene sheet. In conclusion, the incorporation of PdO into graphene improves the sensitivity of the gas sensor, particularly for detecting NO2, making PdO–graphene a highly suitable material for gas sensing applications.